A new solid oral tablet formulation of posaconazole: a randomized clinical trial to investigate rising single- and multiple-dose pharmacokinetics and safety in healthy volunteers - Krishna, G. (Oxford University Press, 2012)
OBJECTIVES: Posaconazole is an extended-spectrum triazole with proven efficacy as antifungal treatment and prophylaxis. The marketed oral suspension should be taken with food to maximize systemic absorption. A new solid oral tablet has been developed with improved bioavailability that can be administered without regard to food. The aim of this study was to evaluate rising single- and multiple-dose pharmacokinetics, safety and tolerability of the new tablet. METHODS: This was a single-centre, randomized, placebo-controlled, Phase I, rising single- and multiple-dose study of healthy subjects aged 18–65 years who received a posaconazole tablet as 200 mg once daily, 200 mg twice daily or 400 mg once daily. The 24 subjects were studied in two cohorts of 12 subjects each (9 active and 3 placebo). RESULTS: After single or multiple oral dose administration of posaconazole tablets (200 and 400 mg), exposure increased in a dose-related manner. Peak posaconazole concentrations were attained at a median T(max) of 4–5 h. Mean half-life was similar for 200 and 400 mg posaconazole doses (25 and 26 h). The accumulation ratio upon multiple doses over 8 days was ∼3 for 200 and 400 mg once daily and ∼5 for 200 mg twice daily. C(avg) values exceeded 1300 ng/mL. The posaconazole oral tablet was safe and well tolerated, although mild, transient elevations in liver function were reported in some patients. CONCLUSIONS: Posaconazole exposure increased in a dose-related manner. The pharmacokinetics of this new solid oral tablet of posaconazole supports the clinical evaluation of once-daily dosing regimens for fungal infections.